التطور العمرانى والمعماري لمدينة بيت المقدس في صدر الإسلام: (16-132هــ/ 637 – 750م) دراسة تاريخية تحليلية / Sharef Amin Abu shamalla - Sharef Amin, Abu Shamalla (2016)
This thesis examines the development of architecture and urbanism arts in Jerusalem from the early Islamic period which started with the Islamic Conquest till the end of the Umayyad (16-132 H/ 637- 750 C.E) within the framework of architectural and historical research in order to recognize the phases and features of this development in the Holy City amongst its historical, political and social contexts and to get acquainted with the historical experience philosophy of the first Islamic Era and how it deals with previous Heritage. The goal can be achieved by studying the main architectural and urban landmarks of Jerusalem, and dividing them into two groups for analysis: religious architecture such as Al-Aqsa Mosque, Qebli Mosque, Salsala Dome, the Dome of the Rock and the Gates, and civil architecture such as Umayyad Palaces Complex, residential buildings and important infrastructure such as the water system. Then this study categorizes the characteristics which distinguish the architecture of Jerusalem formally and structurally by using two methods: the historical analytical approach and the archaeological architectural approach. This study of Jerusalem’s architecture and urbanism illustrates how the Muslims succeeded in protecting and achieving their political, cultural and religious privacy by applying their civilized message in the face of many challenges at that time.